Estimating Labor Supply Responses Using Tax Reforms - Blundell, Richard; Duncan, Alan; Meghir, Costas (Econometrica, 1998)
[The 1980's tax reforms and the changing dispersion of wages offer one of the best opportunities yet to estimate labor supply effects. Nevertheless, changing sample composition, aggregate shocks, the changing composition of the tax paying population, and discontinuities in the tax system create serious identification and estimation problems. We develop grouping estimators that address these issues. Our results reveal positive and moderately sized wage elasticities. We also find negative income effects for women with children.]